Integrating Relationship and Influencer Marketing to Enhance Repurchase Intention Through the Pillars of Satisfaction and Trust - Anik Isniati; Mohamad Rifqy Roosdhani; Ali Ali (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to analyze the effect of relationship marketing and influencer marketing on repurchase intention with customer satisfaction and customer trust as mediating variables among PT Arminareka Perdana's Umrah pilgrims in Jakarta. Method: This study uses a quantitative approach with a survey design. The research sample consisted of 125 Umrah pilgrim respondents selected using purposive sampling. Data collection was conducted through a structured questionnaire, then analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test the relationship between variables. Results: The results show that relationship marketing and influencer marketing have a positive and significant effect on repurchase intention, customer satisfaction, and customer trust. In addition, customer satisfaction and customer trust are proven to mediate the effect of relationship marketing and influencer marketing on repurchase intention. Implications: The findings of this study indicate that the application of relationship marketing strategies and the use of credible influencers can increase pilgrims' satisfaction and trust, which ultimately encourages repeat purchases. The results of this study have practical implications for umrah travel agencies in formulating effective marketing strategies and can serve as a basis for further research by adding different variables or research objects